The Relationship between the Application of Sustainable Principles and Students' Waste Segregation Behavior at SMAN 1 Singosari - Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Durrotul Qomaria; Andien Sahira Fitrinia; Rutmini Martauli Pakpahan (Universitas Tidar, 2022)
The principle of sustainability is applied as an effort to preserve the environment, especially the school environment. The application of sustainable principles is related to student behavior in sorting waste in schools. This study aims to determine the relationship between the application of sustainable principles and students' waste sorting behavior in the SMAN 1 Singosari environment. This study used a survey method and sample selection using the purposive sampling technique. Data were obtained through an online questionnaire containing statements related to sustainable principles and waste sorting behavior distributed through Google Form. The data obtained were then analyzed using the Pearson correlation test. The results showed that there was a strong correlation between the application of sustainable principles and students' waste sorting behavior with a Pearson correlation value of 0.689 and the form of the relationship between the two variables, namely positive.